Outsourced internal audit function and audit report timeliness in an emerging economy: The moderating effect of client-specific expertise - Nahla Abdulrahman Mohammed Raweh; Abdulwahid Ahmed Hashed Abdullah (Cogent Business & Management, 2023)
Motivated by the increasing interest of auditing regulators, organizations, and researchers in outsourced internal audit function (OIAF), this paper examines how outsourced IAF provider is connected with timely audit reporting, and particularly explores the moderating influence of client-specific expertise on the relationship between outsourced IAF provider and audit report timeliness. A sample of Omani-listed firms over the period 2013-2019 and pooled regression analysis with robust standard errors are utilized. The findings reveal that the external IAF provider is slightly related to reduced delay in the audit report. In particular, the reduction is more pronounced when the external IAF provider has client-specific expertise and increases audit timeliness. These results are robust after conducting a sensitivity analysis. This paper presents the importance of outsourced IAF providers, particularly those with clients' expertise, in supporting the best practices of external audits and timely reporting.
Keywords: 650; audit report timeliness; client-specific expertise; internal audit function (IAF); outsourced IAF providers